(untitled) (Research, Society and Development, 2021)
This research aimed to identify in the Common National Curriculum Base (BNCC, in the Portuguese acronym) indications of didactic situations that foster students’ protagonism. Didactic situations allow teachers to prepare students to face social demands as well as help students learn to know, learn to do, learn to interact, learn to become citizens and, learn to be protagonists of their learning. To this end, the study supported by a qualitative approach used a protocol for the document analysis organized according to the following themes: competences and skills and, didactic situations as a curricular principle. Based on this, the research aimed to identify excerpts that indicated potential experiences that allow students to become protagonists of their learning process. These keywords guided the analysis: strategy, activity, protagonism, problem situations, methodology, self-reflection, metacognition, self-evaluation and reflection. The data generated was analyzed according to Content Analysis technique. The results demonstrate there is a concern for using various strategies and teaching resources that stimulate students to act as protagonists, as well as the use of Communication and Information Technologies, research and problem solving methods. Thus, allowing teachers to create didactic situations that provide students´ active learning and the education of critical and aware students.